(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Children is a loving couple, the parents should be responsible for the health and welfare of their children. Child welfare is alive bearing the security, tranquility, and prosperity for children both spiritually and temporally. Prosperous state will be achieved when a child needs both spiritual and physical can be fulfilled, then the need for it in an effort to achieve these goals, which can be a way of increasing the economic income families or the elderly. The growth and development of children is the result of an interaction between genetic factors-hereditaryconstitutional and environmental factors, both prenatal and environmental surroundings postnatal the growth of children affected by dietary factors (nutrition) and genetic. Objective: To improve the nutrition of children in order to obtain optimal growth in the region of 2 health centers Sewon Bantul. Objective: In a study that will be conducted by researchers, the objectives to be achieved are: to improve child nutrition in order to obtain optimal growth in the area of health centers Sewon 2 Bantul. Methods: This study was a quantitative study using a study design was cross-sectional. This type of research is cross sectional. In this type, the independent and dependent variables assessed simultaneously at any one time, so there was no follow-up Results:The higher the mother’s knowledge, the better growth in children. Knowledge contributes to the growth of children as an effort to improve child nutrition. an increase in the mother’s knowledge will be in line with the growth of children. The knowledge of the mother is associated with the growth of children, which depicts a mother in caring for her child in the subject of children’s growth as undertakings improving child nutrition Conclusion: There is a relationship between maternal knowledge about nutritional needs balanced with the growth of the child in an effort to improve gisi child health centers in the region of 2 Sewon Bantul Keywords: Knowledge, balanced nutrition